To Study the Behavior of Compacted Soil Using Basalt Fibers (International Journal of Innovative Research in Engineering & Management, 2022)
This study has been conducted to find out  the mechanism and effect of basalt fiber on compacted soil.  For this study a series of Unconfined Compressive  Strength, California Bearing Ratio tests, Atterberg limits  and Proctor compaction tests have been conducted on soil  reinforced with basalt fiber. The various contents of basalt  fibers are considered in this paper. Fibers are dispersed into  respective soil at contents of 0.15%, 0.20%, 0.25 and  0.30%, under constant length of 12 mm, experimental  results shows that basalt fiber can effectively improve the  Atterberg’s limits, UCS and CBR of reinforced soil. The  results have shown that the Maximum Dry density of soil  increases by 18.01% when 0.30% of basalt fibers mixed  with the given soil. The Unconfined compressive strength  of soil also increases by 380% when 0.30% of basalt fibers  were mixed in the soil sample. The best content was found  at 0.15% of basalt fiber were MDD, UCS and CBR values  of soil increases rapidly. The study has shown that the  strength of soil increases with the inclusion of basalt fibers  by reducing the liquid limit and plastic limit, The plasticity  index decreases by 62.64% which indicates that the  properties of soil being improved.
Keywords: CBR; OMC; MDD; UCT; UU